ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL OPERASI BENTUK ALJABAR BERDASARKAN TEORI KASTOLAN - Ajeng Rena Fujirahayu; Aflich Yusnita Fitrianna; Luvy Sylviana Zanthy (IKIP Siliwangi, 2022)
The purpose of this research is to find out students' mistakes in solving algebraic operations according to Kastolan's theory. In this study used a qualitative descriptive method with the research subject of class VII in one of the MTs in West Bandung Regency with a total of 20 students consisting of 9 girls and 11 boys. The data collection technique was carried out in the form of a written test consisting of 5 description questionsFrom the results of the analysis of student errors based on Kastolan theory, there are several types of Kastolan errors overall, namely: 1) the type of conceptual error is 60%, this type of error is included in the high category 2) the type of procedural error is 40%sufficient category and 3) the type of technical error by 30% this type of error is included in the low category. Based on the results of the analysis that has been obtained from students' answers, the cause of the errors that exist in each of these errors is an error in making mathematical models, students do not show completion strategies and students' lack of ability to perform arithmetic operations.